2024
DOI: 10.1002/aelm.202300643
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Nanoplatelet Integrated Thermally Drawn PVDF Triboelectric Nanocomposite Fibers for Extreme Environmental Conditions

Md Sazid Bin Sadeque,
Mahmudur Rahman,
Md Mehdi Hasan
et al.

Abstract: Triboelectric nanogenerators (TENGs) utilize the synergetic effect of triboelectrification and electrostatic induction to guide electrons through an external circuit, enabling low‐frequency mechanical and biomechanical energy harvesting and self‐powered sensing. Integrating 2D material with a high specific surface area into flexible ferroelectric polymers such as polyvinylidene difluoride (PVDF) has proven to be an efficient strategy to improve the performance of TENG devices. Scalable fabrication of graphene‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 130 publications
(158 reference statements)
0
6
0
Order By: Relevance
“…In a recent study, Sadeque and colleagues successfully fabricated graphene-integrated PVDF nanocomposite fibers using a hot stretching process and employed them in the production of TENGs [ 117 ]. The experimental findings illustrate that the addition of 5% graphene to PVDF fibers markedly improves their electrical performance, resulting in a respective increase of 1.41 times and 1.48 times in Voc and Isc.…”
Section: Regulation Strategies For Enhancing the Performance Of Tengs...mentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, Sadeque and colleagues successfully fabricated graphene-integrated PVDF nanocomposite fibers using a hot stretching process and employed them in the production of TENGs [ 117 ]. The experimental findings illustrate that the addition of 5% graphene to PVDF fibers markedly improves their electrical performance, resulting in a respective increase of 1.41 times and 1.48 times in Voc and Isc.…”
Section: Regulation Strategies For Enhancing the Performance Of Tengs...mentioning
confidence: 99%
“…Sadeque et al demonstrated the scalability in graphene-integrated PVDF nanocomposite fibers using a hot stretching technique, marking the first instance of such a demonstration [ 117 ]. The incorporation of 5% graphene into PVDF fibers resulted in a respective increase of 1.48 and 1.41 times in Isc and Voc ( Figure 15 a,b).…”
Section: Application Prospect Of Ferroelectric Materials In Various T...mentioning
confidence: 99%
See 3 more Smart Citations